2 × 9 = 81 conversely and 9 × 9 = 18 conversely” Mathematic play of 9- year-old, the copyright and the civil law (Discourse of Law and Administration, 2024)
Nine-year-old student of the second class of primary school has observed (discovered?) specific feature of multiplication table referring to multiplication by 9. It appears it might have some value for children mathematic education. In this article I consider whether, after meeting other requirements, such observation might be protected by copyright. Its protection as personal good is unquestionable to me.
Keywords: multiplication table; student; copyright; personal good